Early-life maternal attachment and risky health behaviours in adolescence: findings from the United Kingdom Millennium Cohort Study - Beatrice D. Reyes; Dougal S. Hargreaves; Hanna Creese (BMC, 2021)
Abstract Background Early uptake of multiple risky behaviours during adolescence, such as substance use, antisocial and sexual behaviours, can lead to poor health outcomes without timely interventions. This study investigated how early-life maternal attachment, or emotional bonds between mothers and infants, influenced later risky behaviours in adolescence alongside other potential explanatory pathways using the United Kingdom Millennium Cohort Study. Methods Total maternal attachment scores measured at 9 months using the Condon (1998) Maternal Postnatal Attachment Scale compared higher and lower attachment, where mothers in the lowest 10th percentile represented lower attachment. Multiple risky behaviours, defined as two or more risky behaviours (including smoking cigarettes, vaping, alcohol consumption, illegal drug use, antisocial behaviour, criminal engagement, unsafe sex, and gambling), were scored from 0 to 8 at age 17. Five multivariate logistic regression models examined associations between maternal attachment and multiple risky behaviours among Millennium Cohort Study members (n = 7796). Mediation analysis sequentially adjusted for blocks of explanatory mechanisms, including low attachment mechanisms (multiple births, infant prematurity, sex, breastfeeding, unplanned pregnancy and maternal age at birth), maternal depression, and social inequalities (single-parent status, socioeconomic circumstance by maternal education and household income) at 9 months and poor adolescent mental health at 14 years. Results Children of mothers with lower maternal attachment at 9 months had 23% increased odds of multiple risky behaviours at 17 years (OR: 1.23, 95% CI: 1.00-1.50) in the unadjusted baseline model. All five explanatory blocks attenuated baseline odds. Low attachment mechanisms attenuated 13%, social inequalities 17%, and poor mental health 17%. Maternal depression attenuated the highest proportion (26%) after fully adjusting for all factors (30%). Conclusions Lower maternal attachment in early life predicted increased adolescent multiple risky behaviours. Almost a third of the excess risk was attributable to child, maternal and socioeconomic factors, with over a quarter explained by maternal depression. Recognising the influence of early-life risk factors on adolescent health could innovate current policies and interventions addressing multiple risky behaviour uptake affecting health inequalities across the life course.